CARBON SIZE AND TEMPERATURE EFFECTS TO JIS S45C CARBURIZED STEEL - Ekaputra, I Made Wicaksana; Wibisono, Yustinus Akas; Haryadi, Gunawan Dwi (Jurnal Rekayasa Mesin, 2024)
Wear on a metal can be naturally found in components that operate in a friction environment, such as in a transmission system. However, it can be a substantial problem when the wear rate is not within the permitted limit. Surface hardening is a popular way to improve surface wear resistance for metals with various parameters that can be controlled during the process. In this study, pack carburizing was conducted for plain carbon steel JIS S45C. The carburizing process is conducted on the steel by varying the carbon size and temperature during the heating process. The carbon size consisted of mesh sizes of 5 and 15. The heating process was conducted for 2 hours at 800oC and 900oC. The carbon media and catalyst used in this study were coconut charcoal and calcium carbonate (CaCO3). In addition, the hardness Vickers test was conducted to evaluate the surface hardness. It was found that the hardness of Vickers increased with an increase in heating temperature and mesh size of carbon.